TRENDS IN THE DEVELOPMENT OF MEDICAL TOURISM IN GLOBALIZATION (IN THE EXAMPLE OF TURKEY) (Development Service Industry Management, 2023)
The article is devoted to identifying the peculiarities and prospects of the development of medical tourism in Turkey in the context of the globalization of the medical space, as well as in the context of the implementation of this experience in Ukraine. The paper defines the theoretical foundations of the study of the concept of "medical tourism". The terminology of medical tourism has been clarified, and the characteristic features, varieties, and peculiarities of the organization and geography of travel for recovery and treatment have been revealed. And the peculiarities of the organization of medical tourism against the background of the global popularization of a healthy lifestyle and the simultaneous deterioration of the state of health of modern people and the improvement of their well-being are substantiated.The world trends in the development of medical tourism and international medical tourism, as a specific type of socially useful activity aimed at providing medical and recreational tourism services in the form of a temporary departure of an individual or a group of persons abroad, have been studied. Based on the analysis of international experience, the types of treatment most in demand by medical tourists have been determined. The main reasons for the colossal gap in the cost of medical services of the leading countries and countries with emerging markets have been identified. An assessment of the socioeconomic and political prerequisites for the development of medical tourism in Turkey was carried out, as well as the current state of development of medical tourism in this country was investigated. An assessment of the prospects and problems of the development of medical tourism in Turkey was carried out in the context of the implementation of this experience in Ukraine and an assessment of the opportunities and ways of further development of medical tourism in Ukraine. A certain base has already been developed and there is potential for the development of medical tourism, but the problems that inhibit it remain unresolved. For the more active development of the medical tourism system in Ukraine, it is necessary to create an effective model of marketing policy in health care, improve the material base and introduce modern medical technologies, change legislation, undergo international certifications, improve service and raise the quality of services to a higher level.
Keywords: medical services; medical tourism; medical industry; tourism industry; global segment